Rechargeable metal-metal alkaline batteries : Recent advances, current issues and future research strategies - Jahidul, Islam; Rubel, Anwar; Mahmud, Shareef; Hossain M., Zabed; J.N., Sahu; Xianghui, Qi; Mayeen Uddin, Khandaker; Arthur, Ragauskas; Imed, Boukhris; Md Rezaur, Rahman; Faisal Islam, Chowdhury (Elsevier Science, Ltd., 2023)
Over the past few decades, remarkable advancement has been attained in the field of rechargeable metal–metal alkaline batteries (RABs). In terms of safety, energy density, charge-discharge capacity, and long-term storage capability, metal-metal RABs (e.g., Ni–Zn, Ni–Fe, Ni–Bi, Ni–MH, Ag–Zn, Co–Zn, Cu–Zn, and Bi–Zn systems) are contemplated as the promising energy storage devices for the applications in electric vehicles (EVs), hybrid EVs, grid-scale energy storage, as well as various implantable and wearable electronic devices. Especially, Ni-MH batteries become competitive with Li-ion batteries for EVs and hybrid EVs applications due to their high tolerance against mechanical abuse, stability under wide temperature ranges, and considerable charge/discharge capacity. Meanwhile, earlier works reviewed only specific topics, so, as a rapidly growing research topic, providing a deep understanding on metal–metal RABs is timely and worthwhile. So, in this work, we discuss the electrochemistry of all metal-metal RABs, then full cell designing with their performance will be discussed thoroughly. Further, issues associated with the existing metal–metal RABs and corresponding improv